Relationship of parenting styles on depression, anxiety, stress and self-esteem of adolescents - Rabina Khadka; Anjali Bhatt; Milan Thapa; Anusha Sharma; Manoj Joshi; Durga Khadka Mishra (PLoS ONE, 2025)
Globally, fourteen percent of adolescents suffer from mental health issues. Among the many contributing factors to mental health problems, parenting is considered to have a significant effect on both the physical and psychological health of adolescents. This study aimed to assess depression, anxiety, stress, and self-esteem among adolescents and their relationship with parenting style. A community-based cross-sectional study with multistage proportionate sampling was conducted among 583 school-going adolescents from 15 th September to 14 th October 2022 in Bheemdatt Municipality. This study used the previously validated Depression Anxiety and Stress Scale-21 (DASS-21), Rosenberg Self-Esteem Scale, and Parenting Style and Dimension Questionnaire to assess the status and relationships. Variables were analyzed using a multivariate logistic regression model, and a p-value of <0.05 was considered statistically significant. The prevalence of depression, anxiety, and stress among adolescents was found to be 37.39% (95% CI: 33.46 to 41.32), 42.19% (95% CI: 38.18 to 46.19), and 24.69% (95% CI: 21.18 to 28.19), respectively. Likewise, the mean self-esteem score among adolescents was found to be 22.26 ± 3.56. The authoritative parenting style was found to be significantly associated with DAS and self-esteem among adolescents, while authoritarian parenting style is associated with depression and self-esteem, and permissive parenting style is associated with stress. Social support, and bullying, showed strong effects on the research outcomes. These findings highlight the crucial role of parental involvement and support in shaping adolescent mental health, underscoring the need for positive parenting practices to improve mental health outcomes for adolescents. It is highly recommended that school-based programs focus on raising awareness of mental health issues and offer interventions such as stress management and student counseling. There is a pressing need to effectively monitor and enforce anti-bullying policies within educational settings.